Electrostatic self-assembled graphene oxide-collagen scaffolds towards a three-dimensional microenvironment for biomimetic applications - Girão, André F. (2018)
In light of the importance of collagen, one of the most abundant proteins in mammals, the preparation of collagen-based scaffolds is gaining interest in the field of tissue engineering. However, there is a need to develop strategies to produce collagen three dimensional structures with mechanical properties suitable for proper handling and manipulation. In this regard, we report here a self-assembled GO-collagen (GO-Col) scaffold with a porous network resulting from preferential interaction of oxygen functional groups located on the GO nanosheet edges with amine groups on the biopolymer chain. The accurate control of such conjugation, which is dependent of both the pH of the medium and the collagen/GO weight ratio used during the synthesis, allows to minutely modulate the repulsion and bonding forces within the GO-Col nanocomposite system and consequently also provides the opportunity to fabricate a wide range of stable GO-Col scaffolds. Results concerning the stability in physiological medium under mechanical stimulation and the cytocompatibility of the most viable GO-Col scaffold in terms of mechanical integrity and its reduced counterpart indicated that these novel scaffolds provide a useful new approach for the assemblage of suitable cellular microenvironments that could be explored on tissue engineering applications